Junge Perspektiven der Türkeiforschung in Deutschland: Band 1 - Kreiser, Klaus; Motika, Raoul; Steinbach, Udo; Joppien, Charlotte; Schulz, Ludwig (Springer Nature, 2014)
Türkeiforschung; Türkei; Nachwuchsforschung; Migration; Integration; Politisches System der Türkei